The impact of the external environment on performance of small and medium sized enterprises (SMEs): Evidence from Mekong River Delta, Vietnam : - Vo, Van Dut (Can Tho University, 2008)
This study employs fixed and radom effect model to analyse the impact of the externl environment on SME's performance in MRD, Vietnam. The primary data used in this analysis is surveyed from 33 manufacturing and services,...